Documenting capacity and existing gaps in reporting adverse events following immunisation in Northern Ghana: a quantitative cross-sectional survey of healthcare workers - Daniel Weibel; Abraham Oduro; Miriam Sturkenboom; Nana Akosua Ansah; Samuel Tomilola Oladokun; Enyonam Duah; Patrick Ansah (BMJ Publishing Group, 2023)
Background Immunisation remains an indispensable tool in preventing infectious diseases. A robust pharmacovigilance system assures the public of vaccine safety, particularly in countries like Ghana where there is relatively low reporting of adverse events following immunisation (AEFIs). We explored the experiences of health workers in Ghana to ascertain the existing capacity for data collection and information reporting flows for health events associated with vaccination in the country.Methods We conducted a cross-sectional quantitative survey among healthcare workers (HCWs) in Ghana between December 2020 and April 2021. We documented their experiences with regard to knowledge, perceptions and practice of reporting AEFIs to the national pharmacovigilance centre (Ghana Food and Drugs Authority).Results Out of 851 participants, 49.2% said their institutions had processes for AEFI reporting. Additionally, 25% of participants had encountered an AEFI within the past year. Out of this number, 55% reported the AEFI. Only 31.2% of community health nurses (vaccinators) considered AEFI reporting part of their job description. Most HCWs (59.34%) had fair to poor knowledge of AEFIs. The main factors affecting AEFI reporting were heavy workload and lack of time (54.1%) and unavailability of reporting forms (57.5%). Only 2% of participants were aware AEFIs could be reported online. Logistic regression analysis revealed female gender as a negative factor influencing AEFI reporting. Training (p<0.0001) and profession (p=0.006) significantly influenced knowledge level of AEFIs. Results of the multiple binary logistic regression indicate that the age and profession of HCWs are the main factors influencing knowledge of reporting AEFIs.Conclusion The vaccine pharmacovigilance system in Ghana can be strengthened with targeted regular training on AEFI reporting, guidelines for reporting in all health facilities and prompt feedback from the national pharmacovigilance centre to health workers.